Employees' attitude toward remote work and its challenges in practice after COVID-19 restriction in China : A case study of an E-commerce company - Lu, Xin Yao; Orel, Marko, 1986-; Lukeš Rybanská, Ivana, 1991-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
The Post- COVID-19 policy bring a huge impact on people’s work and life. Since the COVID-19 restrictions no longer exist, China is undergoing a transformation regarding remote work. Without lockdown, the employers need to decide if they would go back to the entirely off-site work mode or keep the remote work mode. The thesis’s aim is to o study remote work after COVID control, employee attitudes; the changes in their work and lives; and the difficulties for remote offices in Chinses SMEs. The goal is to fill in the research gap and provide some reference significance for those SMEs owners to decide. The study is divided into two parts, the theoretical part and the practical part. In the practical part, the research conducted qualitative data research method, conducting 14 semi-structured interviews with the employees of a case E-commerce company. The author used a purposive sampling method, selecting samples from 3 different departments, which are sales, IT and finance. In terms of data analysis, the author analyzed the data via thematic analysis. The key findings of the research showed that employees hold positive attitudes toward remote work and expect to develop in the future. From the individual perspective, remote work is changing family well-being, commute time, communication, work time and workload. There are distractions which also change the employee’s mind to change, for example, improving their living places or hardware. From the organizational perspective, they are changing the support for remote work. The challenges from the employees during remote work are miscommunication, work-life conflict, and insufficient hardware. In addition, they described their future expectation for remote work development of this company. According to the key findings, recommendations for the company in three aspects were proposed.
What’s more, limitations of this research are claimed, and suggestions for additional research avenues are provided in the thesis.
Vedoucí práce: Marko Orel
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses